A FEIRA DE CIÊNCIAS COMO INSTRUMENTO PARA PROMOÇÃO DA APRENDIZAGEM SIGNIFICATIVA NO ENSINO DE CIÊNCIAS. - SILVA, Taise Helena de Sousa (2019)
In this work, the conceptions and procedures for the construction and implementation of Science Fairs used as an instrument for the significant learning of science content in elementary school Early years of basic education units, Anil Nucleus, in the municipality of São Luís/MA, were analyzed. The theoretical framework that assisted the path of discussions was understood in Delizoicov and Angotti (2011), Selbach (2010) that underlie Science Teaching; Ausubel (1968 and 1978) Significant Learning, Mancuso (1993 and 2000) Science Fair, Chassot (2000 and 2003) Scientific Literacy. In documentary research, supported by the constant review of the National Curriculum Guidelines for Basic Education (2013) and the PCN's for Sciences (BRAZIL, 1997 and 1998), Law of Guidelines and Base of National Education - LDB (BRAZIL, 1996) and Common National Curriculum Base - BNCC (BRAZIL, 2016) documents that guide the curricular basis of Science Teaching in Brazil. The stages of research were outlined in the perspective of qualitative research using the precepts of the documentary and participant approach and the use of a questionnaire as an instrument for data collection that vectorized the discussions for content analysis, enabling the construction of a "Outline stits and Strategies for the Implementation of Science Fairs" as a product of this research. It is noteworthy that the research field, as well as the participant subjects, were included in selection criteria observing the peculiarities and formative needs of the public school, in order to contribute to the dynamics of these institutions at the fundamental level, present in the state of Maranhão. The conclusions revealed that the conceptions of the subjects in relation to the Science Fair and its use in Basic Education are of great value for significant learning of the contents of Sciences, for the development of technical-scientific activities and incentive for Scientific Literacy in Elementary School, besides presenting itself as an event well seen by teachers and perceived as a facilitator for the sharing of scientific knowledge, also assisting in the development of those involved in what education by research. It is expected with this study to contribute discussions, reflections and perspective changes in the school context, especially regarding the need and importance of new teaching methodologies and the use of instruments to promote meaningful learning.